Alienation in Families and the Breakdown in Children’s Educational Process: Ann Tyler’s Teenage Wasteland (1983) - Zennure Köseman (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
This research article highlights that postmodern era after the modern period causes fragmentation because of the existence of alienation and isolation senses in family units and ends up undesirable failure in children’s educational process as reflected in American writer Ann Tyler’s Teenage Wasteland. Thereby, these are concurrently the basics of modernism that destructs human lives. Similar to T. S. Eliot’s The Waste Land, Tyler emphasizes the existence of a dramatic monologue deriving from the disillusionment in the infertile land and the alienation in social living. Tyler specifies the presence of a meaningless life and alienation for children. At the same time, Tyler concerns how parents become unable to deal with their children in their intensive working life. She hints that children become unsuccessful in their educational process due to their parents’ intensive working. Therefore, the teenager and his parents have mutual lack of communication in their alienated worlds. A “wasteland” in the target short story implies having the sense of loneliness which causes failure in children’s educational world and rises the disturbance in family units. Accordingly, family members are the victims of their working life and embrace the senses of alienation and isolation in their inner worlds. Therefore, this article will pursue a psychoanalytical consideration in the selected short story.